CONSCIOUS HUMAN RESOURCE MANAGEMENT FOR PEACEBUILDING: A MULTICULTURAL ISLAMIC EDUCATION PERSPECTIVE - Siti Sumadiyah; Maskuri Maskuri; Junaidi Mistar (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to provide a descriptive explanation, analytical insight, and interpretive understanding of the following issues: (1) the role of conscious human resource management (HRM) in fostering institutional peace within an increasingly multicultural society; (2) the implementation of value-based HRM approaches that integrate spiritual awareness and intercultural principles within multicultural Islamic educational institutions; and (3) the internalization of multicultural Islamic values such as tawassuth (moderation), tasamuh (tolerance), ta’aruf (mutual understanding), and ta’awun (mutual assistance) in HRM practices. Positioned within the framework of multicultural Islamic education, this research employed a qualitative case study design. Data were collected through semi-structured interviews, participatory observation, and documentation, and were analyzed using datacondensation, data display, and conclusion drawing. The findings reveal that conscious HRM contributes to the enhancement of self-awareness, emotional intelligence, and inclusive interpersonal relationships, thereby cultivating a peaceful organizationalculture. These findings enrich the concept of value-based HRM rooted in spirituality and offer policy insights, particularly in the development of institutional education and training policies based on multicultural and Islamic spiritual values. Accordingly, thisstudy provides practical contributions not only to educational institutions and local communities but also to policymakers in designing HRM training models that support transformative, sustainable, and responsive peacebuilding in the context of Indonesia’s multicultural society